2003
DOI: 10.1128/mcb.23.20.7198-7209.2003
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 Is a Direct PERK Substrate and Effector of PERK-Dependent Cell Survival

Abstract: Activation of PERK following the accumulation of unfolded proteins in the endoplasmic reticulum (ER)promotes translation inhibition and cell cycle arrest. PERK function is essential for cell survival following exposure of cells to ER stress, but the mechanisms whereby PERK signaling promotes cell survival are not thoroughly understood. We have identified the Nrf2 transcription factor as a novel PERK substrate. In unstressed cells, Nrf2 is maintained in the cytoplasm via association with Keap1. PERK-dependent p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
900
4
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,105 publications
(942 citation statements)
references
References 46 publications
33
900
4
5
Order By: Relevance
“…[126][127][128] Therefore, a loss of Nrf2 function may partly explain why PERK À/À cells experience increased oxidative stress in response to perturbations in ER function. 108 Consistent with this model, Nrf2 À/À cells are sensitized to ER stress, 125 providing another way in which PERK signaling promotes cell survival.…”
Section: Esr In Mammalsmentioning
confidence: 72%
See 1 more Smart Citation
“…[126][127][128] Therefore, a loss of Nrf2 function may partly explain why PERK À/À cells experience increased oxidative stress in response to perturbations in ER function. 108 Consistent with this model, Nrf2 À/À cells are sensitized to ER stress, 125 providing another way in which PERK signaling promotes cell survival.…”
Section: Esr In Mammalsmentioning
confidence: 72%
“…124 The bZIP transcription factor Nrf2 was recently identified as a second substrate of PERK. 125 Upon ESR induction, PERK phosphorylation causes Nrf2 to relocalize from the cytoplasm to the nucleus, where it upregulates a range of antioxidant response genes. [126][127][128] Therefore, a loss of Nrf2 function may partly explain why PERK À/À cells experience increased oxidative stress in response to perturbations in ER function.…”
Section: Esr In Mammalsmentioning
confidence: 99%
“…However, very high concentrations of metformin (5 m m ) were required to observe significant inhibition of mitochondrion respiratory chain complex 1 activity (He & Wondisford, 2015). Recent studies showed that Nrf2 can be activated by the ER unfolded protein response sensors IRE1α (Hourihan, Moronetti Mazzeo, Fernandez‐Cardenas, & Blackwell, 2016) and PERK (Cullinan et al., 2003). However, in our hands, PERK activation was not detected when HDFs were treated with 100 μ m metformin (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…NRF2 also induces the expression of anti-oxidant responsive genes (Chen and Kunsch 2004). This is possibly the response to high oxidative stress in these recombinant CHO cells as a result of continuous and repeated folding processes inside the stressed ER (Cullinan et al 2003).…”
Section: Dynamics Of Perk Signaling Branch Of Upr Pathwaymentioning
confidence: 98%